Determinants of Exclusive Breastfeeding Practices of Female Healthcare Workers in Jakarta, Indonesia - Rapingah, Siti; Muhani, Nova; Besral, Besral; Yuniar, Poppy (UI Scholars Hub, 2021)
The World Health Organization (WHO) recommended that mothers worldwide exclusively breastfeed their infants for the child's first six months to achieve optimal growth, development, and health. Indonesia had not fulfilled the global standard of breastfeeding rate so that there was low coverage of exclusive breastfeeding in East Jakarta, especially for female healthcare workers. This study aimed to determine the factors associated with exclusive breastfeeding practices of healthcare workers. This was a quantitative study using a cross-sectional design. The recruited sample consisted of 85 female public health center workers with infants aged 6-24 months. Data were collected using self-administered questionnaires. Logistic regression analysis was applied to identify factors associated with exclusive breastfeeding. The results showed that the proportion of exclusive breastfeeding was 54.1%. Variables associated with exclusive breastfeeding were knowledge, attitude, family support, co-worker support, and healthcare worker support. Multivariate analysis showed that knowledge and age were the dominant factors of exclusive breastfeeding practices with an odds ratio (OR) adjusted OR of 14 and 5, re¬spectively. Knowledge was an influential factor in the success of exclusive breastfeeding. Therefore, creating a training program related to breastfeeding would be expected to improve knowledge. Besides, a supportive policy such as providing breastfeeding facilities was needed.